(untitled) (Clinics, 2015)
OBJECTIVES: To determine the serum interleukin-17 (IL-17) levels in childhood-onset systemic lupus erythematosus patients and to evaluate the association between IL-17 and clinical manifestations, disease activity, laboratory findings and treatment. METHODS: We included 67 consecutive childhood-onset systemic lupus erythematosus patients [61 women; median age 18 years (range 11-31)], 55 first-degree relatives [50 women; median age 40 years (range 29-52)] and 47 age- and sex-matched healthy controls [42 women; median age 19 years (range 6-30)]. The childhood-onset systemic lupus erythematosus patients were assessed for clinical and laboratory systemic lupus erythematosus manifestations, disease activity [Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)], cumulative damage [Systemic Lupus International Collaborating Clinics/American College of Rheumatology (ACR) Damage Index] and current drug use. Serum IL-17 levels were measured by an enzyme-linked immunosorbent assay using commercial kits. RESULTS: The median serum IL-17 level was 36.3 (range 17.36-105.92) pg/mL in childhood-onset systemic lupus erythematosus patients and 29.47 (15.16-62.17) pg/mL in healthy controls (p=0.009). We observed an association between serum IL-17 levels and active nephritis (p=0.01) and migraines (p=0.03). Serum IL-17 levels were not associated with disease activity (p=0.32), cumulative damage (p=0.34), or medication use (p=0.63). CONCLUSION: IL-17 is increased in childhood-onset systemic lupus erythematosus and may play a role in the pathogenesis of neuropsychiatric and renal manifestations. Longitudinal studies are necessary to determine the role of IL-17 in childhood-onset systemic lupus erythematosus.